ANALISIS AKTIVITAS PROMOSI PRODUK WILDTRACK APPAREL - Nur Dyatin, Rochmad; Wangi, Maya Sekar; Widiyowati, Estu (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
This research is motivated by the phenomenon of the inability of several creative industries to maximize the capabilities of human resources and the use of communication media in supporting promotional activities in their companies. The purpose of this study is to analyze the promotional activities of Wildtrack Apparel products. This study uses the promotion theory according to Kotler and Armstrong as a reference for research using descriptive qualitative research methods. The sampling technique is done by purposive sampling. Data collection is carried out through observation of Wildtrack Apparel product promotional activities, interviews with owners, marketing, employees and consumers as well as documentation related to the company's promotional activities. The validity test techniques used by researchers are method triangulation and source triangulation. The results of the study indicate that Wildtrack Apparel product promotional activities include the application of marketing mix with a communication approach that utilizes the development of information technology and a social relations approach to build a positive corporate image so as to increase sales of Wildtrack Apparel products. Thus, the promotional activities carried out by Wildtrack Apparel have been able to strengthen communication with consumers to market products and increase sales of Wildtrack Apparel products optimally.